To study the effectiveness of solid waste collection and transportation system around Kuantan municipal housing area - Sharul Rizuan , Ismail (2013)
Solid waste collection and transportation system is one of the important elements in solid waste management. Population growth and rapid economic development requires an effective solid waste collection and transportation system. This is important to avoid the various problems that may arise due to the increasing of solid waste generation from day to day. In addition, an effective collection system can reduce the cost of solid waste management, as 5 0-80% of the management cost is contributed by collection and transportation activities. Therefore, a study on the effectiveness of the solid waste collection and transportation system has been conducted around Kuantan municipal housing area to see its effectiveness. Residences involved in this study were Taman Seriku, Taman Seri Mahkota, Taman Indera Mahkota 5 and Taman Indera Mahkota 6. Data collection methods used in this study is weighing the waste generated by the population in the study area three times a week before collection work is carried out. In addition the questionnaire method was also used in this study in order to get data about collection data at study area. Data was analyzed using Microsoft Excel. Data were analyzed from various aspects such as the weight of waste produced per household before garbage collected, the frequency of garbage collection performed, ethics and view of residents with existing collection system. Results showed that the collection and transportation system around Kuantan municipal housing area is good and effective, but there are some small problems that need to be look up to avoid any problems in the future.